Financial stability as a precondition for the financing of sustainable development in emerging and developing countries - Ingo Bordon; Birgit Schmitz (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
On 25 September 2015 the 2030 agenda for sustainable development was passed at the summit of the United Nations in New York. This agenda sees the Sustainable Development Goals (SDGs) replace the Millennium Development Goals (MDGs), which draw to a close in 2015. The new agenda follows a universal approach and will apply to developing, emerging and developed countries alike. It should also form the basis for a changed global partnership. The 17 Sustainable Development Goals link the principle of sustainability with economic, environmental and social development. Financing plays a key role in the realisation of the objectives. In addition to trade, technology, the strengthening of local capacities and coherent international co-operation, financing is of paramount importance. Shortly before the passing of the 2030 agenda the financing of sustainable development was also discussed intensively within the scope of the 3rd UN Conference on Financing for Development. One of the goals of the Addis Ababa conference was to safeguard and improve the financing of sustainable development, particularly in developing countries. The necessary basis for this is a stable financial system, as a regional or global financial crisis could endanger the new development agenda. The final document places its priorities on the intensification of domestic resource mobilisation, the reliable disbursement of the funds for development co-operation and on tapping new resources of financing for developing countries. However, it does not address the role of financial stability in sufficient depth. The choice of financing sources and instruments has a decisive influence on the stability of the financial system. During the global economic and financial crisis there was also a close interrelation between the financing structure and the effects of the crisis on the real sector. With the implementation of the 2030 agenda for sustainable development the question is raised as to whether the use of supplementary and new sources of financing fundamentally alters the financial structure in emerging and developing countries and what effects on financial stability are to be anticipated. This depends primarily on the financing conditions of a country. Secondly, the structure of the financial system plays a role because the size and breadth of the financial system and the role of cross-border financing determine the ability of the financial system to withstand systemic shocks. Thirdly, financing in order to achieve specific sustainable development goals can lead to new systemic risks. Its specific risk and financing profile makes the energy sector an example of this. The risks to financial stability always need to be taken into account in the financing of investments in order to achieve the new sustainable development goals. On the one hand, the emerging and developing countries need to improve on managing financial complexity. On the other hand, more stringent international financial market regulation and more intensive co-ordination are required. This would enable the risks to financial stability to be contained and not used as an excuse for postponing investment in sustainable development.
Keywords: 330; Entwicklungsfinanzierung und öffentliche Finanzen; Internationales Finanzsystem